TINJAUAN YURIDIS TERHADAP PERTIMBANGAN HAKIM DALAM PEMIDANAAN TINDAK PIDANA NARKOTIKA YANG DIPUTUS MINIMUM KHUSUS DIKAITKAN DENGAN PARADIGMA POSITIVISME HUKUM (Studi Kasus Beberapa Putusan Hakim dalam Perkara Tindak Pidana Narkotika di Pengadilan Negeri Pekanbaru ) - Rani Juwita; Mexsasai Indra; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The judges' verdict criminal cases narcotics in the sentenced criminal special minimum District Court Pekanbaru background research , narcotics in violation of Law No. 35 Year 2009 on Narcotics , judges convict to the minimum penalty specifically with Article 127 paragraph ( 1 ) letter a is 2 years in prison . The judge gives a decision against the defendant narcotic crime away from the threat of the minimum set by law . In this case the judges tend to think in terms of moral judgment and is based with factual evidence or rational argument . Not like the flow of legal positivism . Where the flow of legal positivism is a way of thinking that is just under the Act . From the research problem there are two things that can be inferred . First, the verdict is essentially a work of finding the law , which stipulates what should be according to the law in any event concerning life in a state of law . If it is associated with Positivism Legal positivism where the essence of the law is that the law is a command. At the time of this verdict the judge considered to be true because it is still in accordance with the legislation . Second, the imposition of a special minimum punishment in sentencing purposes deemed not appropriate . Because of the special minimum criminal punishment only see things any mitigating for the accused and it is enough to provide justice for defendants not to provide a deterrent effect or retaliation against crimes that have been committed by the perpetrator.Keywords : Basic Considerations - Judge - Narcotics - Minimum Special Criminal - Legal Positivism